13=(x+7)/3

Simple and best practice solution for 13=(x+7)/3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 13=(x+7)/3 equation:



13=(x+7)/3
We move all terms to the left:
13-((x+7)/3)=0
We multiply all the terms by the denominator
-((x+7)+13*3)=0
We calculate terms in parentheses: -((x+7)+13*3), so:
(x+7)+13*3
We add all the numbers together, and all the variables
(x+7)+39
We get rid of parentheses
x+7+39
We add all the numbers together, and all the variables
x+46
Back to the equation:
-(x+46)
We get rid of parentheses
-x-46=0
We add all the numbers together, and all the variables
-1x-46=0
We move all terms containing x to the left, all other terms to the right
-x=46
x=46/-1
x=-46

See similar equations:

| 3x+3.3=2x-2.1 | | 25c^2−5c−16=-4 | | x/2+x-1/3-x+1/4=1 | | X-3=6+8x-2 | | -4y-6y-4=56 | | 4(×-2)=3x-10 | | 9x-1=4x-9 | | 9x+67=2x+23 | | 22x=-143+33x | | 1/5a-1-5=-6 | | x2+6x+8=24 | | 5x-30=3x-18+2x | | 9x+3(3x-8)=30 | | 402=2(4w) | | 3n^2+8n+16=3n | | 1/5t+2=1 | | 402=2(3w+w) | | 324=w(w+15) | | 16p-4=4(2p–3) | | -7x+14=4x-19” | | 11x+8=(-3) | | |2x+6|=2|5+x| | | 20y+5=81/4 | | 8d+2(3-d)=30 | | (3x-10)+(2x-10)=90 | | 2(v+2)=-3-2v | | 19=-4x+1 | | 5x+14=7x+14-2x | | 20=-4(1-x)+3(x+1) | | 15=4y-15-7y | | 6x-7/7=-7 | | -4h=28 |

Equations solver categories